Engineered Cathode Buffer Layers for Highly Efficient Organic Solar Cells: A Review. Issue 19 (30th January 2022) - Bishnoi, Swati; Datt, Ram; Arya, Sandeep; Gupta, Sonal; Gupta, Ramashanker; Tsoi, Wing Chung; Sharma, Shailesh N.; Patole, Shashikant P.; Gupta, Vinay
Abstract: This article presents an in‐depth insight into the most efficient cathode buffer layers (CBLs) in conventional and inverted organic solar cells (OSCs). The CBL can play a critical role in improving the short circuit current density ( J sc ) and fill factor (FF) of the devices by minimizing the contact resistance and reducing charge recombination at electrode/photoactive layer interface, resulting in the efficient extraction of charge carriers and therefore improving the power conversion efficiency (PCE). This review explores CBL with respect to its effect on the physics of a device and electronic processes at the interface of CBL/photoactive layer and its impact on the overall performance of OSCs. Besides this, the role of CBL, its chemical composition, morphology, thickness, dopants, deposition conditions, etc., and their corresponding effects on the device performance of both conventional and inverted OSCs are discussed in detail. Finally, CBLs that provide the best performance are summarized and their chemical structures are discussed. This article will benefit the researchers working in the domain of OSCs by providing an understanding of the CBL layers, along with various interfacial processes. Abstract : This article gives a consolidated overview of the cathode buffer layers (CBL) reported for organic solar cells (OSCs) in conventional and inverted device architecture. It explains in detail the working mechanism and the processing of CBL materials to improve the overall efficiency and lifetime of OSCs with elaborated examples.